APLIKASI DECISION SUPPORT SYSTEM MODEL FUZZY TAHANI UNTUK PENENTUAN DAERAH PROMOSI PENERIMAAN MAHASISWA BARU STMIK NURDIN HAMZAH: SISTEM PENDUKUNG KEPUTUSAN, LOKASI PROMOSI, FUZZY TAHANI, PHP, MYSQL - Kahar, Novhirtamely; Wahyuning Astuti, Reny; Firmansyah, Andi (FORTECH (Journal of Information Technology), 2018)
High School of Informatics and Computer Management Nurdin Hamzah Jambi is one of the institutions of Higher Education in the field of education Strata One requires data sources and data processing appropriate for the determination of the location of new student admissions campaign efficiency and accuracy of data that can support the process of retrieval decisions well and appropriately. Determination Process of Promotion Area during this system used still be manual that member or promotion team determine location only based on existing school in area of Jambi City without seeing aspect or other criteria that can be level of measuring promotion. Overcome this, the purpose of making a new student admissions decision support system is to process the data into the criteria by becoming the best alternative alternative in the decision-making process, so that the decision-making process can be generated information quickly, accurately and accurately in accordance with the needs. Input used in the form of location data, and data criteria in need, then produce output in the form of recommendation information of the promotional areas become a priority. Tools used are PHP Web programming languages that use Codeigniter Framework, and MySQL Database. With the implementation of the New Student Admission Decision Support System is expected to help facilitate the promotion team members in the process of determining the location and the resulting information will be more quickly and accurately.